Spontaneous generation of beta-limiting MHD modes in tokamaks - Shirokov, M.S.; Mikhailovskii, A.B.; Konovalov, S.V.; Tsypin, V.S. (Вопросы атомной науки и техники, 2003)
It is shown that under conditions typical of fusion reactors of tokamak type, a spontaneous generation of magnetohydrodynamic (MHD) modes is possible, which may limit plasma pressure in ideally stable plasma. Electromagnetic field of such modes consists of two different scale lengths: a large-scale (MHD) component and a small-scale one, which is smaller than Larmor radius of thermal ions. It is suggested that these modes can be responsible for spontaneous generation of neoclassical tearing modes observed experimentally. The value of threshold beta for this mode onset was found to be similar to that in experiments showing NTMs.